The Effectiveness of Picture Storybooks for Flood Disaster Emergency Drill for Children Aged 5-6 Years in Raudhatul Athfal Ar-Razzaq - Rezki Rahmadona; Sean Marta Efastri; Azlin Atika Putri (Universitas Lancang Kuning, 2024)
This study was conducted with the aim of determining the effectiveness of picture story books on the understanding of children aged 5-6 years about flood relief emergency drills in Raudhatul Athfal Ar-Razzaq. This study uses the Pre-Experiment design experimental method with the type of One-Group Pretest-Posttest Design, the design of this method is to find out how much influence an equivalent sample has. The data obtained produces statistical t with a calculated t value of 18,326 and sig. 0.000 ≤ 0.05 means significance data. Based on the results that have been described, it can be concluded that there is an effectiveness of picture story books in children's understanding of flood disaster emergency drills for children aged 5-6 years in Raudhatul Athfal Ar-Razzaq.